Intervensi Relaksasi Benson pada Pasien Diabetes Mellitus Tipe II dengan Masalah Ketidakstabilan Kadar Glukosa Darah: Studi Kasus - Ni Kadek Sinta Mutiara Dewi; I Wayan Surasta; I Ketut Suardana (Jurnal Gema Keperawatan, 2022)
Prevalence of patients with diabetes mellitus who need hospital treatment due to blood sugar instability problems is still high. The purpose of this study was to describe benson relaxation interventions in patients with type II diabetes mellitus with blood sugar instability through nursing care. This research uses a case study method with a nursing care approach. The results of the study found data on the study of nursing patients complaining of weakness or lethargy, dry mouth, increased thirst and high blood glucose levels of 374 mg/dL. The formulated nursing diagnosis is the instability of blood glucose levels associated with insulin resistance. The outcomes of care in the form of stability of elevated blood glucose levels and the main interventions of hyperglycemia management, interventions supporting dietary education, as well as innovative interventions of benson relaxation therapy are given 3 times a day for 10-15 minutes. The implementation of nursing is carried out in accordance with the planned nursing plan for 3 times 24 hours. The nursing evaluation showed that the goal was achieved as evidenced by weakness or decreased lethargy, moist mouth, decreased thirst and improved blood glucose levels of 184 mg/dL. Benson relaxation therapy can be an intervention used to deal with the problem of instability of blood glucose levels in patients with type II diabetes mellitus.